Objective-C for iPhone developers : a beginner's guide - Brannan, James A. (New York : McGraw-Hill, 2010)
Create your own iPhone and Mac OS X applications with ease. Objective-C for iPhone Developers: A Beginner's Guide shows you how to use the Objective-C programming language, Apple's Foundation framework, the iPhone SDK, and the Xcode development environment. The first stop for aspiring iPhone developers, this hands-on guide teaches you how to create versatile, innovative, and marketable apps in no time. Real-world examples throughout the book correspond with downloadable Xcode projects and video tutorials so you can get started with your first app right away. Designed for Easy Learning Key Skills & Concepts--Chapter-opening lists of specific skills covered in the chapter Ask the Expert--Q&A sections filled with bonus information and helpful tips Try This--Hands-on exercises that show you how to apply your skills Notes--Extra information related to the topic being covered Tips--Helpful reminders or alternative ways of doing things Annotated Syntax--Example code with commentary that describes the programming techniques being illustrated.
Keywords: Objective-C (Computer program language); Object-oriented programming (Computer science); iPhone (Smartphone) -- Mobile apps